Ancient Schwannoma of the Cauda Equina: Our Experience and Review of the Literature. (22nd December 2016) - Wierzbicki, Venceslao; Pesce, Alessandro; Marrocco, Luigi; Piccione, Emanuele; Frati, Alessandro; Caruso, Riccardo
Abstract : Ancient schwannomas (AS) are exceedingly rare variant of common schwannomas (CS). Only two cases involving the cauda equina region have been previously reported in literature. AS are typically associated with a higher histological degree of degenerative changes (Antoni B areas). It is of peculiar importance, according to our opinion, to outline that, because of their extremely slow growth (which explains the increase of the degenerative changes in respect to the CS) and their typical soft consistency in respect to their standard counterparts, AS usually imply an even better prognosis.